Design of a Web-Based Medical Warehouse Inventory System at Bhayangkara TK-II Hospital Medan - Siholnang Sitindaon; Hafni; Muhammad Zen (Cattleya Darmaya Fortuna, 2026)
The development of information technology has driven a transformation in healthcare service management, including in the management system of medical warehouse inventory in hospitals. Bhayangkara Hospital TK II Medan, as a referral hospital, has complex and ongoing medical logistics needs, requiring an effective and accurate inventory management system. However, inventory systems that are still manual or semi-computerized pose various problems, such as discrepancies between stock data and physical conditions, delays in information on item availability, difficulties in monitoring expiration dates, as well as the risk of stock shortages or overstocking. This study aims to design a web-based medical warehouse inventory system capable of managing data centrally and in real-time. The research methods used include system requirements analysis, system design, and web-based system implementation. The results of this study are expected to produce an inventory system that facilitates recording of incoming and outgoing goods, monitoring of stock and expiration dates, and the presentation of accurate reports. With this system, it is anticipated that the management of the medical warehouse inventory at Bhayangkara Hospital TK II Medan will become more effective and efficient and support improvements in healthcare service quality.